Proses Terbentuknya Perilaku Konsumtif Remaja Perempuan dengan Pola Pikir Orientasi pada Brand (Brand Minded) pada Produk Fashion: ( Studi Fenomenologi Siswi SMA Trimurti Surabaya) - Dante, Aish; Dewi, Putri Aisyiyah Rachma (The Commercium, 2021)
Consumptive actors can happen to anyone, including teenagers, and teenage girls have a higher tendency to consumptive behavior than boys. Consumptive behavior of teenage girls occurs when they seeproducts fashion attractivethat are in front of their eyes. This research was conducted as a material for discussing how the process of forming consumptive behavior experienced by Trimurti High School girls who have amindset brand minded in fashion products. In this study, it is also explained about the process of forming the consumptive behavior of teenage girls from Trimurti High School Surabaya with a brand-oriented mindset on fashion products. The process goes through the stages of introduction to branded fashion products by parents, finding self-identity by using branded fashion, getting to know directly when in a shopping center (mall), getting to knowproducts branded fashion from their environment, being interested in branded fashion and finally getting to the stage. purchase continuity.